Influence of Organizational Commitment and Work Culture on Job Satisfaction of General Section Employees of the Bontang City Regional Secretariat - Takwin, Muhammad; Hidayat, Nur Aulia; Hijrawati, Hijrawati (Universitas Muhammadiyah Palu, 2024)
This research was conducted to determine the influence of organizational commitment and work culture on job satisfaction of employees in the general section of the Bontang City Regional Secretariat. This research is a type of quantitative research. The respondents in this study were 50 employees of the General Section of the Bontang City Regional Secretariat. Data was processed using SPSS version 16.0. The results were tested using multiple regression analysis, F test, t test and R2 test. In the multiple linear regression test, Y= 12.924 + 0.256X1 + 1.019X2. F calculation shows a value of 154.694 with a significance level of 0.000. Meanwhile, the F table value is 3.20. This shows that the Fcount value is > Ftable with a significance level of 0.000 <0.05. Testing the tcount value for the Organizational Commitment variable (X1) is greater than the t table value (4.717 > 2.010) with a significance level below 0.05, namely 0.000. Meanwhile, the tcount value for the Work Culture variable (X2) is greater than the t table value (8.796 > 2.010) with a significance level below 0.05, namely 0.000. The R Square value was 86.8%. This means that the independent variables Organizational Commitment and Work Culture together influence the dependent variable Job Satisfaction by 86.8% and the rest is influenced by other variables not included in this research. From these results it is shown that Organizational Commitment and Work Culture together have a significant effect on Job Satisfaction for Employees of the General Section of the Bontang City Regional Secretariat.